KEYNOTE 3. Race to the Finish: Our Evolving Understanding of the Role of Active Mobility for a Sustainable Future (Baltic Journal of Sport and Health Sciences, 2026)
The week after HEPA Europe 2025, political leaders from around the world will meet in New York at the Fourth High-LevelMeeting of the United Nations General Assembly on the prevention and control of non-communicable diseases and the promotion of mental health and well-being (HLM4). They will gather with the ambition of adopting a Political Declaration to correctthe course towards 2030, based on the fndings of a progress report showing that, more than halfway to 2030, the world is noton track to meet the commitment to reduce by one third premature mortality from non-communicable diseases (NCDs) throughprevention and treatment and promoting mental health and well-being by 2030 (target 3.4 of the Sustainable Development Goals,SDGs)1.In this challenging context, multisectoral action for NCDs prevention and control emerges as one of the key priority areas toaccelerate progress. A key positive driver for action is the growing understanding of the positive role of active mobility on topand above the NCD agenda, allowing to make progress simultaneously on a number of the SDGs, most notably those related toGood health and well-being (SDG3), Reducing inequalities (SDG10), Sustainable cities and communities (SDG11), and ClimateAction (SDG13).Recognising the links between active mobility and the multiple societal aspirations it may contribute to can be highly empowering for policy makers, professionals, and civil society organisations from diﬀerent policy and disciplinary perspectives, if theycan see their own stakes supported. The WHO European Centre for Environment and Health has worked with experts and representatives of Member States from diﬀerent sectors and competences to bring together the best available evidence underpinningadvocacy arguments supporting the promotion of active mobility. The result of this work is a social media campaign launched onWorld Bicycle Day, targeting diverse audiences and presenting them with “100 reasons for walking and cycling”.Taking an evolutionary perspective, the intervention will explain how scientifc evidence from a range of disciplinary domainshas been brought together to advocate the positive role of active mobility for health, the environment, society, and the economy,because “Whatever your reason, walking and cycling are the best ways to move forward”.